Evaluation of two harvesting procedures for oil palm (iElaeis guineensis/i Jacq.) fruits. A case study (2017)
This study was performed in Las Brisas Oilseed property located in the Municipality of Puerto Wilches, province of Santander, Colombia. It was evaluated a harvesting procedure that modifies the traditional procedure adding an implement called “pepero” placed on the plate of the palm below the cluster for let the fruit to fall in it after the cutting process. With this procedure, it was not necessary to clean thoroughly the plates, as the fruits were few to collect. Using these method at least two herbicide applications over the plate can decrease annually and for the same reason leaf residues dropped from the pruning would reach their decomposition process, promoting the palm root system growth, thereby, increasing the absorption of nutrients from the fertilizer. During the evaluation, the proposed method reduced 63% of the harvest efficiency, however it was noted that adjusting harvest cycles to avoid clusters of mature young palms and working performance could be improved. We presented very promising application with the hybrid GOX which is replacing current materials as palm, this has small growth and has the tendency to attach the fruits, even than overriped.